(untitled) (Salam International Academic Journal, 2011)
Whilst the war in Afghanistan continues, there has been an obvious challenge to the acute medical services to necessarily priorities the demands of on-going illness and injury. In focusing on this, little attention has been given to the effects of the war on mental health. This brief paper aims to highlight the extent of mental illness in Afghanistan, identifying the most common problems and makes reference to strategic considerations for developing services.